Systematic review of the literature on islamic religious education design in indonesia: the role of parents in islamic religious education - Nurhasnawati, Nurhasnawati; Alwizar, Alwizar; Syafaruddin, Syafaruddin; Darmawati , Darmawati; MFZ, M. Fahli Zatrahadi; HKM, Hakmi Wahyudi; ISQ, Istiqomah (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
The majority of Islamic religious education institutions still segregate themselves from public education. The purpose of this study is to analyze the design of Islamic religious education in Indonesia. Research methods utilizing the systematic literature review (SLR) refer to methods for finding, judging, and interpreting all available literature related to the formulation of problems or areas of topics studied. Nvivo software was used to help analyze the research data. There are 72 documents discussing the design of Islamic education. However, after screening according to the criteria, there are only 10 documents left that are then analyzed. Document data is obtained through a dimensional database. Research results show that there are four main themes that have the most potential in the discussion of Islamic education design. The four sub-themes include integration of Islamic values in the education system, shift of the Islamic education paradigm, hadith concept in Islamic religious education, and the role of parents in Islamic religious education. This is related to the design of Islamic religious education in Indonesia.